Influence of pH of sol-gel solution on phase composition and photocatalytic activity of TiO2 under UV and visible light. (December 2016) - Tryba, B.; Tygielska, M.; Colbeau-Justin, C.; Kusiak-Nejman, E.; Kapica-Kozar, J.; Wróbel, R.; Żołnierkiewicz, G.; Guskos, N.
Graphical abstract: Highlights: Preparation of TiO2 at pH = 10 with NH4 OH and HT in air at 400 °C causes narrowing of Eg. Such prepared TiO2 is active under visible light due to formation of Ti 3+ and NO2 2− . High crystallinity of anatase and low value of ς extend lifetime of free charges. Abstract: Nanocrystalline TiO2 was prepared in the sol-gel method by hydrolysis of titanium (IV) isopropoxide (TIP) at the different pH: autogenic, pH = 10 (with ammonia solution) and pH = 3 (with acetic acid solution). The obtained materials were calcined at 400 °C. Time Resolved Microwave Conductivity (TRMC) analyses showed, that the highest lifetime of charge-carriers was obtained for sample prepared at pH = 10 calcined at 400 °C, which exhibited highly crystallised anatase phase and the lowest value of ς potential. Preparation of TiO2 with an ammonia solution and its further calcination at 400 °C caused reduction of Ti 4+ to Ti 3+ in the bulk, narrowing of the band gap with formation of an extra band above the valence band of TiO2 assigned to formed NO2 2− species. Such prepared photocatalyst showed extended lifetime of free charges under UV irradiation in comparison with the other prepared samples and activity under visible light.